De jure versus de facto: Exchange rate stabilization in Central and Eastern Europe - Gunther Schnabl (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2003)
The IMF classifications of the Central and Eastern European exchange rate arrangements are heterogeneous. While one group of countries reports tight pegs to the euro, a second group seems to have moved toward (more) exchange rate flexibility. Based on the recent discussion about the accuracy of IMF exchange rate arrangement classifications, low- and highfrequency exchange rate stability in Central and Eastern Europe is explored here. In this paper we find that de facto exchange rate stabilization is much more prevalent in Central and Eastern Europe than suggested by de jure exchange rate classifications. Most of the CEE countries peg their currencies to the euro, thereby contributing to a growing euro zone. Nevertheless, as exchange rate stabilization against the euro is pursued with different degrees and with different long-term drifts, intra-regional exchange rates are still far from being unified.
urn:nbn:de:bsz:21-opus-18573
Keywords: F31; F33; 330; Foreign Exchange Policy; EMU; Euro Zone; Central and Eastern Europe; Wechselkurspolitik; Stufenflexibilität; Euro; Europäische Wirtschafts- und Währungsunion; Osteuropa